Green Marketing Strategies and Consumer Purchasing Decisions: An Analysis of Environmental Awareness as a Moderator - Agus Cholik; Andi Kurniawati (Global Research Collaboration, 2026)
This study examines the influence of green marketing on consumer purchasing decisions by positioning environmental awareness as a moderating variable. The research was motivated by the increasing public concern regarding environmental sustainability, which has encouraged companies to adopt environmentally oriented marketing strategies to influence consumer behavior. However, the effectiveness of green marketing practices remains dependent on the extent to which consumers possess environmental awareness and ecological responsibility. This study employed a quantitative explanatory research design using a survey method. Data were collected from 300 consumers who had previously purchased environmentally friendly products in several urban areas in Indonesia. The sampling technique applied was purposive sampling, while data analysis was conducted using SPSS version 27 through descriptive statistics, validity and reliability testing, classical assumption testing, multiple linear regression analysis, and Moderated Regression Analysis (MRA). The findings reveal that green marketing has a positive and significant effect on consumer purchasing decisions. Environmental awareness also positively influences purchasing decisions and significantly strengthens the relationship between green marketing and consumer purchasing decisions. These results indicate that consumers with higher environmental awareness are more responsive to sustainability-oriented marketing strategies and more likely to support environmentally friendly products. The study contributes theoretically by extending sustainable marketing literature through the integration of environmental awareness as a moderating variable. Practically, the findings provide strategic insights for companies in developing authentic green marketing initiatives and strengthening environmental education to encourage sustainable consumer behavior.